2007
DOI: 10.5012/bkcs.2007.28.4.538
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Lead(II)-selective Electrode Based on N,N'-Bis-thiophen-2-ylmethylene-pyridine-2,6-diamine as an Ion Carrier

Abstract: Polymeric electrodes for lead ion based on N,N'-bis-thiophen-2-ylmethylene-pyridine-2,6-diamine as an ion carrier were prepared. The membrane electrode (m-3) containing o-NPOE as a plasticizer and 50 mol% additive of ionophore gives an excellent Nernstian response (29.59 mV/decade) and the limit of detection of -log a (M) = 5.74 to Pb 2+ in Pb(NO3)2 solution at room temperature. The prepared electrode provided good sensitivity and outstanding selectivity and response for Pb 2+ over a wide variety of other meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…It is observed that C21H19N3O2S and C21H18N3OSCl ligands are more active against the fungal and bacterial strains A. Nigar and S. aureus as compare to other fungal and bacterial strains. Other ligands are moderately active against all fungal and bacterial strains 36,37 Antibacterial activities are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that C21H19N3O2S and C21H18N3OSCl ligands are more active against the fungal and bacterial strains A. Nigar and S. aureus as compare to other fungal and bacterial strains. Other ligands are moderately active against all fungal and bacterial strains 36,37 Antibacterial activities are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%